Pengaruh Ekstrak Etanol Daun Binahong (Anredera Cordifolia (Tenore) Steen) Terhadap Penyembuhan Luka Sayat Pada Tikus Putih Jantan - Aried Eriadi; Helmi Arifin; Zet Rizal; Barmitoni Barmitoni (Jurnal Farmasi Higea, 2015)
Wound healing is a normal process as responds by the skin tissue injury. This research is purposed to see the effects of ethanol extract in binahong leaf to  healing the wound of male white rats. There are rats which are divided into five treatment groups, group I (negative control), group II is given providone iodine 10% (positive control), group III, IV and V are given the extract of binahong leaf ointment consist of 5%, 10%, 15% for each. By making a wound on the back of the rats about 20 mm long and 2 mm deep. The ointment is applied based on the treatment for each group twice a day during ten days, the lenght count every day by using caliper. The data is analyzed by using two ways ANOVA and continued by Duncan Test. The result showed that ethanol extract in binahong leaf can heal the wound in scale concentration about 10%-15%, length of wound was decrease on seventh day. The more extract concentration given, the more effect in wound healing